Indonesian Children‘s Readiness for Elementary School: a Preliminary Study to the Holistic Approach to School Readiness - Pangestuti, Retno; Agustiani, Hendriati; Cahyadi, Surya; Kadiyono, Anissa L. (Pedagogika, 2018)
Gross enrolment rate of the participation of Indonesian children in Early Childhood Education has been increasing significantly every year. Ideally, it should be followed by an increase in children‘s readiness for elementary school as its main goal. However, the readiness of new students in the first grade of elementary school is still considered low in some aspects. The objectives of this research are to: 1) explore the perception of children’s readiness for elementary school, according to the paradigm of teachers and parents, and 2) describe the aspects and indicators that are considered important for children’s readiness for elementary school. The methodology of this research used qualitative case study. Participants involved amounted to 83, consisted of 43 teachers and 40 parents. Data were collected through Focus Group Discussion in teacher and parent groups also observations during group discussion process. The results of the study conclude three issues related to the children’s readiness for elementary school: 1) readiness of children for elementary school in Indonesia is perceived dominant in the academic domain, 2) there are 6 aspects, 20 sub-aspects and 83 indicators of children’s readiness for elementary school which were formulated in this study. Additional aspects cover moral and religious values. This also becomes the ‘state of the art’ of this research which may not be found in the concept of elementary school readiness in other countries.